A renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy and its preparation method

By using refining agents and thermal treatment processes of specific components in thermal casting magnesium alloy, the problem of purity and material uniformity of magnesium alloy melts are solved, and high purity, uniformity and high strong toughness are achieved, which significantly improves magnesium magnesium The performance of the alloy.

CN118895447BActive Publication Date: 2025-01-28SHANDONG HAIHUA GRP CO LTD +1

Patent Information

Application Number
CN202411385109.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of melt purification and material uniformization of heat-free die-cast magnesium alloys, resulting in high hydrogen content and large inclusions, which affects strength and toughness and anti-hydrogen embrittlement characteristics.

Method used

A renewable heat -free treatment high -strong die -casting magnesium alloy containing AL, RE, MN, ZR, FE and other components is composed of specific thermal treatment processes and refining agents, including CACL2, BACL2, CAF2, MGCO3, bromide, ZR2fe, ZR2fe Alloys and KCL components of refining agents are performed by pyrine protection resistance furnace treatment and magnesium oxide porous ceramic filtrates to achieve high purity and uniformity of magnesium alloy.

Benefits of technology

实现了镁合金的高纯净度和均匀化,氢含量低于0.5ml/100g Mg,夹杂体积分数低于0.1%,压铸态抗拉强度可达295MPa,屈服强度可达188MPa,延伸率最高可达 22%, significantly improved the strength of the magnesium alloy and the hydrogen anti -hydrogen crisps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895447B_ABST
    Figure CN118895447B_ABST
Patent Text Reader

Abstract

The present invention discloses a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy and a preparation method thereof, and relates to the technical field of magnesium alloy materials. The weight percentages of the components of the renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy are Al: 3.0-6.0%, RE: 4.0-6.0%, Mn: 0.2-1.0%, Zr: 0.1-0.5%, Fe: 0.03-0.15%, Si≤0.001%, Ni≤0.001%, the remainder is Mg, and RE is selected from any one of the rare earths La, Ce and Y. The die-cast magnesium alloy phases include matrix α-Mg, Al4RE, Al2RE and Zr2Fe phases; and have excellent toughness and high resistance to hydrogen embrittlement. The method of the present invention can use recycled waste magnesium with complex composition and more impurities as raw material to manufacture high-strength and toughness heat-treatment-free die-cast magnesium alloy, which can reduce manufacturing costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloy materials, and in particular to a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy and a preparation method thereof. Background Art

[0002] The content of magnesium in the earth's crust is about 2.1%~2.7%, ranking fourth among all metal elements. my country is the country with the richest magnesium resources in the world, with available magnesium reserves accounting for 70% of the world's total reserves, of which magnesite reserves rank first in the world. The prospective reserves of magnesium salt mineral resources in the four major salt lakes reach billions of tons. my country's magnesium production and export volume have ranked first in the world for ten consecutive years. Magnesium alloys are praised as "one of the most promising lightweight green materials in the 21st century" due to their low density (density is only 2 / 3 of aluminum alloys and 1 / 4 of steel), good biocompatibility and electromagnetic shielding properties. At present, my country's external dependence on iron ore and lithium ore has reached 82% and 65% respectively. The large-scale application of magnesium alloys has very important strategic significance for energy conservation and emission reduction, and alleviating the shortage of metal mineral resources in my country.

[0003] In September 2020, Tesla officially announced that the Model Y will use an integrated die-cast rear floor assembly, reducing the number of parts from 70 to 1-2, reducing the total weight of the rear floor by 30%, and reducing the manufacturing cost of the whole vehicle by 40%, which has driven the full follow-up of the leading domestic and foreign car manufacturers. At the same time, it also stimulated and promoted the development of automobile magnesium alloy components from "small size and simple structure" to "large size" and "structural and functional integration". More and more integrated die-cast magnesium alloy large-scale structural parts have appeared. The integrated molding of large-scale magnesium alloy castings integrates dozens or even hundreds of single parts into a large or super-large structural part. Some parts are thin and some parts are thick, and heat treatment is impossible. Otherwise, it will be severely deformed and produce bubbles and have to be scrapped. The development of heat-treatment-free die-cast magnesium alloy materials is the key to realizing the integrated die-casting of large-scale magnesium alloy structural parts, especially to solve the challenges of heat-treatment-free die-cast magnesium alloy melt purification and material homogenization.

[0004] The challenges of purifying the heat-treatment-free die-casting magnesium alloy melt mainly come from the excessively high melt hydrogen content and inclusions. The gas dissolved in the magnesium melt is mainly hydrogen, and the hydrogen in the magnesium melt mainly comes from the reaction of water in the magnesium melt and flux, moisture adsorbed on the metal surface, and water brought in by metal corrosion. At 700°C, the hydrogen content in the magnesium melt reaches 50ml / 100g Mg, while it is only 9.8ml / 100g Al in aluminum. When the hydrogen content in 100g of magnesium exceeds 14.5ml, microscopic pores will appear in the magnesium alloy, seriously affecting the mechanical properties. In addition to reducing the strength and toughness of magnesium alloy die-castings, the excessively high hydrogen content in magnesium alloys will significantly reduce the fatigue life of die-castings, and lead to hydrogen embrittlement under the induction of external environments such as alternating stress, impact loads, and rain and seawater. Therefore, the hydrogen content in the magnesium melt must be strictly controlled. The Chinese patent document with the publication number CN 116334432 A discloses a method for purifying a rare earth magnesium alloy melt. The five-stage purification technology formed by integrating the refining flux purification, ultrasonic field purification, foam ceramic + wire mesh + iron scraps composite filtration purification method can reduce the hydrogen content in the alloy melt from 32~42ml / 100g Mg to 12.6~23ml / 100g Mg. However, the process steps of this method are complicated, the operation process is difficult to control, and the hydrogen content of the melt after treatment is still too high. The inclusions in the magnesium alloy mainly come from stable oxides that are easily generated during the smelting process. More than 85% of the inclusions in the magnesium alloy are MgO in the form of particles and films. There are often many microscopic holes around the MgO inclusions, namely the so-called "slag gas phase generation". These inclusions not only seriously deteriorate the mechanical properties of the alloy, but also are accompanied by defects such as pores and shrinkage, which reduce the casting performance. In addition, the flux inclusions such as MgCl2 remaining in the magnesium alloy have strong hygroscopicity and will accelerate the corrosion of magnesium alloy castings. The composite impurity removal process of flux refining + sedimentation, which is widely used in the industry, uses flux to capture and wet inclusions, and then wraps the inclusions and settles them to the bottom of the crucible during the subsequent long-term heat preservation and static process to achieve a purification effect, significantly reducing the inclusion content in the melt. The Chinese patent document with publication number CN 102672148 B discloses a new process for purifying magnesium alloys, which purifies magnesium alloys through refining treatment and 730~780℃ heat preservation and static process for 30~100 minutes. However, long-term static will inevitably lead to the separation of light and heavy elements in the melt and the resulting composition and performance segregation of different parts of the casting, which brings huge challenges to the composition uniformity and performance uniformity of large-melting magnesium alloys, especially large magnesium alloy die castings containing heavy elements such as rare earths, and the contradiction between melt purification and composition homogenization is prominent. Summary of the invention

[0005] The purpose of the present invention is to provide a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy. The renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy has extremely low hydrogen and inclusion content, solves the problem of large-scale die-cast magnesium alloy melt purification and material homogenization, has high yield strength, tensile strength and elongation, and exhibits excellent strength and toughness and hydrogen embrittlement resistance.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy, wherein the weight percentages of the components in the die-cast magnesium alloy are Al: 3.0-6.0%, RE: 4.0-6.0%, Mn: 0.2-1.0%, Zr: 0.1-0.5%, Fe: 0.03-0.15%, Si≤0.001%, Ni≤0.001%, the balance is Mg, and RE is selected from any one of the rare earths La, Ce and Y.

[0008] Furthermore, the die-cast magnesium alloy phases include a spherical matrix α-Mg solid solution, a lamellar Al4RE precipitation phase, an Al2RE particle precipitation phase and a Zr2Fe particle phase; the grain size of the spherical α-Mg solid solution is 2 to 6 μm, the lamellar spacing of the lamellar Al4RE precipitation phase is 80 to 100 nm, the precipitation phase Al2RE particle size is 200 to 500 nm, and the median particle size of the Zr2Fe particles is 1 μm; the die-cast tensile strength of the heat-treatment-free die-cast magnesium alloy is 268 to 295 MPa, the yield strength is 160 to 188 MPa, and the elongation is 8.5 to 22%; the hydrogen content of the die-cast magnesium alloy is <0.5 ml / 100 g Mg, and the inclusion volume fraction is <0.1%.

[0009] Another object of the present invention is to provide a method for preparing the above-mentioned renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy, comprising the following steps:

[0010] 1) Put the recycled magnesium ingot, aluminum and aluminum-manganese master alloy into a crucible of an argon-protected resistance furnace, heat it to 700-730°C, add the rare earth metal element after the charge is completely melted, and stir evenly for 15-30 minutes to obtain a magnesium melt;

[0011] 2) The magnesium melt is heated to 730-750° C. for refining, and a refining agent is evenly sprayed into the magnesium melt with argon gas and maintained for 10-20 minutes. After the spraying is completed, the slag is removed and the magnesium melt is allowed to stand for 10-15 minutes; the spraying speed of the refining agent is 0.5-1.2 kg / min, and the argon gas pressure is 0.2-0.6 MPa;

[0012] 3) The magnesium melt refined in step 2) is heated to 750-770° C., kept at this temperature and allowed to stand for 10-20 minutes; the resistance furnace is powered off and cooled to 700-730° C., and then samples are taken for testing to control the impurity content of Si ≤ 0.001% and Ni ≤ 0.001%; ​​the magnesium melt is filtered through a porous magnesium oxide ceramic sheet and then cast into a preheated ingot mold to obtain a heat-treatment-free die-cast magnesium alloy.

[0013] Furthermore, the refining agent in step 2) is composed of the following components in weight fractions:

[0014] CaCl2 20~40%

[0015] BaCl2 6~15%

[0016] CaF2 5~10%

[0017] MgCO3 5~7%

[0018] Bromide 8~15%

[0019] Zr2Fe alloy 3~6%

[0020] The balance is KCl.

[0021] Furthermore, the bromide in the refining agent is any one of MgBr2 and CaBr2. The Zr2Fe alloy in the refining agent is a powder particle with a median particle size of 1 μm obtained by repeated smelting three times in a magnetic suspension smelting furnace and then ball milling and sieving. The tetragonal Zr2Fe "hydrogen pumping" alloy has an extremely low hydrogen adsorption equilibrium pressure, high hydrogen absorption efficiency under low hydrogen content concentration, large hydrogen adsorption capacity and high thermal stability, and the hydrogen adsorption capacity at 20°C is about 120ml / g.

[0022] Furthermore, the refining agent is prepared by mixing the components according to corresponding percentages, feeding them into a ball mill with a rotation speed of 100-300 r / min, grinding them into powder, and then passing through a 20-40 mesh sieve.

[0023] The amount of the refining agent in step 2) is 1.5-3% of the weight of the magnesium melt.

[0024] The pore size of the porous magnesium oxide ceramic sheet in step 3) is 20 to 40 ppi, and the thickness of the ceramic sheet is 20 to 30 mm.

[0025] The present invention has the following beneficial effects:

[0026] The renewable heat-treatment-free high-strength and toughness die-casting magnesium alloy provided by the present invention is a high-purity, homogenized ultrafine-grained die-casting magnesium alloy, whose physical phases include a quasi-spherical matrix α-Mg solid solution, a lamellar Al4RE precipitation phase, an Al2RE particle precipitation phase and a Zr2Fe particle phase. The alloy has a uniform and fine structure and good die-casting process performance. The quasi-spherical α-Mg solid solution with a grain size of 2 to 6 μm, the lamellar Al4RE precipitation phase with a lamellar spacing of 80 to 100 nm, the particle precipitation phase Al2RE with a size of 200 to 500 nm, and the Zr2Fe particles with a median particle size of 1 μm bring about the synergistic effect of solid solution strengthening, fine grain strengthening and dispersion strengthening of high thermal stability precipitation phases, so that the die-casting magnesium alloy has comprehensive characteristics of high strength and toughness, and the tensile strength in the die-cast state can reach 295 MPa, the yield strength can reach 188 MPa, and the elongation can reach up to 22%; the hydrogen content of the die-casting magnesium alloy is less than 0.5 ml / 100 g. Mg, inclusion volume fraction <0.1%.

[0027] In the method of the present invention, a refining agent comprising CaCl2, BaCl2, CaF2, MgCO3, bromide, Zr2Fe alloy and KCl components is provided. CaCl2, which has a good adsorption effect on chloride and inclusions in the alloy, is used to replace MgCl2 as the main slag-forming component, which will not cause the loss of rare earth elements. At the same time, it is matched with the weighting agent BaCl2 to increase the specific gravity of the flux, so that the flux and the alloy are separated more easily and quickly. Adding CaF2 can increase the surface tension between the refining agent and the magnesium melt, promote the separation of non-metallic impurities from the magnesium melt, and improve the stability and refining ability of the flux. At the same time, CaF2 can also remove silicon in the form of SiO2. Adding magnesium carbonate can be thermally decomposed at high temperature to form calcite to dissolve MgO inclusions to form a solid solution. The generated CO2 diffuses outward to form spherical interface foaming, which greatly increases its surface area and improves the ability of the refining agent to adsorb oxidized inclusions. At the same time, the released CO2 gas physically degases the magnesium liquid, further strengthening the refining ability of the refining agent. By adding MgBr2 or CaBr2 bromide, since the radius of bromide ion is larger than that of chloride ion, the ability to attract cations with the same charge decreases, the polarity between ionic compounds is weakened, the surface tension and viscosity between the refining agent and the inclusion interface are reduced, the spreadability of the refining agent in the melt and the adsorption capacity of inclusions are improved, thereby improving the purity of the magnesium alloy. The tetragonal ultrafine Zr2Fe "pump hydrogen" alloy has an extremely low hydrogen adsorption equilibrium pressure, high hydrogen absorption efficiency under low hydrogen content concentration, large hydrogen adsorption capacity and high thermal stability. It can quickly absorb a large amount of hydrogen from room temperature to the liquid-solidus temperature of magnesium alloy and under extremely low hydrogen concentration conditions, and stably solidify in the magnesium alloy in the form of "metallic hydrogen", significantly reducing the hydrogen content of magnesium alloy and avoiding the occurrence of hydrogen embrittlement. At the same time, it can also "take away" hydrogen in rare earth hydrides, thereby improving the utilization rate of rare earths; KCl is the basic component of the refining agent. While improving the stability of the refining agent, it makes the refining agent easy to extend and diffuse, which is conducive to the formation of a protective shell on the surface of the magnesium liquid, protecting the magnesium liquid from high-temperature oxidation and combustion, and ensuring the purity of the magnesium liquid. In summary, it can be seen that the high-density refining agent improves the separation of the refining agent and the melt, and can complete the adsorption, sedimentation and separation of inclusions after a short period of standing for 10 to 15 minutes after the refining agent is sprayed, shortening the melt processing time, and achieving high purity and homogenization of large-volume magnesium alloy melts. During the high-temperature standing and power-off cooling natural sedimentation process after the alloy composition test is qualified, the added Mn element forms a higher density and higher melting point iron-manganese solid solution and manganese-silicon intermetallic compound with impurity elements such as Fe and Si in the recycled magnesium, which settles to the bottom of the crucible during the high-temperature standing process. In the subsequent power-off cooling sedimentation process, the impurity elements such as Fe and Si dissolved in the magnesium can be precipitated, combined with the Mn element and precipitated to the bottom and removed, thereby improving the corrosion resistance of the magnesium alloy; the magnesium melt is filtered through a magnesium oxide porous ceramic sheet with a pore size of 20 to 40ppi and a thickness of 20 to 30mm, and then cast to obtain a heat-treatment-free die-cast magnesium alloy.

[0028] The raw materials such as rare earth metals used in the technical solution of the present invention are low in cost, and recycled waste magnesium with complex composition and high impurities can be used as raw material to manufacture high-strength and toughness heat-treatment-free die-cast magnesium alloys, which can reduce manufacturing costs, improve production efficiency, and reduce costs and increase efficiency for enterprises, thereby promoting the rapid development and application of large-scale die-cast magnesium alloy structural parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD patterns of Zr2Fe alloys used in Examples 1 to 3;

[0030] Figure 2 XRD spectrum of the die-cast magnesium alloy prepared in Example 2;

[0031] Figure 3 This is a scanning electron microscope backscattered electron image of the die-cast magnesium alloy obtained in Example 2, magnified 1000 times;

[0032] Figure 4 This is a 5000x scanning electron microscope backscattered electron image of the die-cast magnesium alloy prepared in Example 2.

[0033] Figure 5 This is a 5000x scanning electron microscope secondary electron image of the die-cast magnesium alloy prepared in Example 2. (The sample was corroded by 5% nitric acid alcohol solution (volume fraction), and the sample was observed on a JEOL JXA-8100 scanning electron microscope (SEM) equipped with an OXFORD 7412 energy dispersive spectrometer (EDS), and the inclusion fraction of the alloy was estimated using Image J software; the phase composition analysis was performed on a D / MAX-RC X-ray diffractometer (XRD) using a Cu target; the plate-shaped tensile specimen was subjected to a room temperature (293K) tensile test on a DNS200 universal material testing machine, and the tensile speed was 2 mm•min -1 . ) DETAILED DESCRIPTION

[0034] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments. Example 1

[0035] The method for preparing the renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy of this embodiment comprises the following steps:

[0036] 1) Put the recycled magnesium ingot, aluminum and aluminum-manganese master alloy into a crucible of an argon-protected resistance furnace, heat it to 700°C, add rare earth La after the charge is completely melted, and stir evenly for 15 minutes to obtain a magnesium melt;

[0037] 2) The magnesium melt is heated to 730°C for refining, and the refining agent is evenly sprayed into the magnesium melt with argon gas and maintained for 10 minutes. After the spraying is completed, the slag is removed and the magnesium melt is allowed to stand for 10 minutes. The spraying speed of the refining agent is 0.5kg / min, and the argon pressure is 0.2MPa. The refining agent is composed of the following components in weight fractions: CaCl2: 20%, BaCl2: 6%, CaF2: 5%, MgCO3: 5%, CaBr2: 8%, Zr2Fe alloy: 3%, and the balance is KCl. The refining agent is prepared by mixing the components according to the corresponding percentages, loading them into a ball mill with a rotation speed of 100r / min, and mixing and grinding them into powder, and then passing through a 20-mesh sieve. The Zr2Fe alloy in the refining agent is a powder particle with a median particle size of 1μm obtained by repeatedly smelting three times in a magnetic suspension melting furnace and then ball milling and sieving, such as Figure 1 As shown in the XRD spectrum, the tetragonal Zr2Fe "pump hydrogen" alloy has an extremely low hydrogen adsorption equilibrium pressure, high hydrogen absorption efficiency at low hydrogen concentration, large hydrogen adsorption capacity and high thermal stability, and the hydrogen adsorption capacity at 20°C is about 120ml / g. The amount of refining agent used is 1.5% of the weight of the magnesium melt.

[0038] 3) The magnesium melt refined in step 2) is heated to 750° C. and kept at this temperature for 10 minutes; the resistance furnace is turned off and cooled to 700° C.; the magnesium melt is filtered through a porous magnesium oxide ceramic sheet and then cast into a preheated ingot mold to obtain a heat-treatment-free die-cast magnesium alloy; the pore size of the porous magnesium oxide ceramic sheet is 20 ppi, and the thickness of the ceramic sheet is 20 mm.

[0039] The present embodiment is a reproducible heat-treatment-free high-strength and tough die-cast magnesium alloy. The weight percentages of the components are Al: 3.0%, La: 4.0%, Mn: 0.2%, Zr: 0.1%, Fe: 0.03%, Si≤0.001%, Ni≤0.001%, and the balance is Mg. The die-cast magnesium alloy phases of the present embodiment include a quasi-spherical matrix α-Mg solid solution, a lamellar Al4La precipitation phase, an Al2La particle precipitation phase, and a Zr2Fe particle phase. The synergistic effect of solid solution strengthening, fine grain strengthening and dispersion strengthening of high thermal stability precipitation phases brought about by the spherical α-Mg solid solution with a grain size of 2 to 6 μm, the lamellar Al4La precipitation phase with a lamellar spacing of 80 to 100 nm, the particle precipitation phase Al2La with a size of 200 to 500 nm, and the Zr2Fe particles with a median particle size of 1 μm makes the die-cast magnesium alloy have high strength and toughness comprehensive characteristics. The die-cast tensile strength of the die-cast magnesium alloy in this embodiment is 268 MPa, the yield strength is 160 MPa, and the elongation is 22%; the hydrogen content of the die-cast magnesium alloy is 0.4 ml / 100 g Mg, and the inclusion volume fraction is 0.09%. Example 2

[0040] The method for preparing the renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy of this embodiment comprises the following steps:

[0041] 1) Put the recycled magnesium ingot, aluminum and aluminum-manganese master alloy into a crucible of an argon-protected resistance furnace, heat it to 710°C, add rare earth Ce after the charge is completely melted, and stir evenly for 20 minutes to obtain a magnesium melt;

[0042] 2) The magnesium melt is heated to 740°C for refining, and the refining agent is evenly sprayed into the magnesium melt with argon gas and maintained for 15 minutes. After the spraying is completed, the slag is removed and the magnesium melt is allowed to stand for 13 minutes. The spraying speed of the refining agent is 0.8 kg / min, and the argon pressure is 0.4 MPa. The refining agent is composed of the following components in weight fractions: CaCl2: 30%, BaCl2: 10%, CaF2: 8%, MgCO3: 6%, MgBr2: 12%, Zr2Fe alloy: 4%, and the balance is KCl. The refining agent is prepared by mixing the components according to the corresponding percentages, loading them into a ball mill with a rotation speed of 200 r / min, and mixing and grinding them into powder, and then passing through a 30-mesh sieve. The Zr2Fe alloy in the refining agent is a powder particle with a median particle size of 1 μm obtained by repeatedly smelting three times in a magnetic suspension melting furnace and then sieving through a ball mill, such as Figure 1 As shown in the XRD spectrum, the tetragonal Zr2Fe "pump hydrogen" alloy has an extremely low hydrogen adsorption equilibrium pressure, high hydrogen absorption efficiency at low hydrogen concentration, large hydrogen adsorption capacity and high thermal stability, and the hydrogen adsorption capacity at 20°C is about 120ml / g. The amount of refining agent used is 2% of the weight of the magnesium melt.

[0043] 3) The magnesium melt refined in step 2) is heated to 760°C and kept at this temperature for 15 minutes; the resistance furnace is turned off and cooled to 715°C; the magnesium melt is filtered through a porous magnesium oxide ceramic sheet and then cast into a preheated ingot mold to obtain a heat-treatment-free die-cast magnesium alloy; the pore size of the porous magnesium oxide ceramic sheet is 30ppi and the thickness of the ceramic sheet is 25mm.

[0044] The present embodiment can regenerate a high-strength and toughness die-cast magnesium alloy without heat treatment. The weight percentage of each component is Al: 4.0%, Ce: 4.5%, Mn: 0.6%, Zr: 0.3%, Fe: 0.09%, Si≤0.001%, Ni≤0.001%, and the balance is Mg. Figure 2 As shown in the XRD spectrum of the die-cast magnesium alloy, the phases of the die-cast magnesium alloy in this embodiment include a spherical matrix α-Mg solid solution, a lamellar Al4Ce precipitation phase, an Al2Ce particle precipitation phase and a Zr2Fe particle phase. Due to the low content of the Zr2Fe phase, no corresponding diffraction peak appears on the XRD spectrum, but Figures 3-5Zr2Fe particles with a median particle size of 1 μm can be clearly observed in the scanning electron microscope image; the spherical α-Mg solid solution with a grain size of 2 to 6 μm, the Al4Ce precipitation phase with a lamellar spacing of 80 to 100 nm, the particle precipitation phase Al2Ce with a size of 200 to 500 nm, and the Zr2Fe particles with a median particle size of 1 μm bring about the synergistic effect of solid solution strengthening, fine grain strengthening and dispersion strengthening of high thermal stability precipitation phases, so that the die-cast magnesium alloy has high strength and toughness comprehensive characteristics. The die-cast tensile strength of the die-cast magnesium alloy in this embodiment is 283 MPa, the yield strength is 175 MPa, and the elongation is 12%; the hydrogen content of the die-cast magnesium alloy is 0.3 ml / 100 g Mg, and the inclusion volume fraction is 0.08%. Example 3

[0045] The method for preparing the renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy of this embodiment comprises the following steps:

[0046] 1) Put the recycled magnesium ingot, aluminum and aluminum-manganese master alloy into a crucible of an argon-protected resistance furnace, heat it to 730°C, add rare earth Y after the charge is completely melted, and stir evenly for 30 minutes to obtain a magnesium melt;

[0047] 2) The magnesium melt is heated to 750°C for refining, and the refining agent is evenly sprayed into the magnesium melt with argon gas and maintained for 20 minutes. After the spraying is completed, the slag is removed and the magnesium melt is allowed to stand for 15 minutes. The spraying speed of the refining agent is 1.2 kg / min, and the argon pressure is 0.6 MPa. The refining agent is composed of the following components in weight fractions: CaCl2: 40%, BaCl2: 15%, CaF2: 10%, MgCO3: 7%, CaBr2: 15%, Zr2Fe alloy: 6%, and the balance is KCl. The refining agent is prepared by mixing the components according to the corresponding percentages, loading them into a ball mill with a rotation speed of 300 r / min, and then grinding them into powder and passing through a 40-mesh sieve. The Zr2Fe alloy in the refining agent is a powder particle with a particle size of about 1 μm obtained by repeatedly smelting three times in a magnetic suspension melting furnace and then ball milling and sieving, such as Figure 1 As shown in the XRD spectrum, the tetragonal Zr2Fe "pump hydrogen" alloy has an extremely low hydrogen adsorption equilibrium pressure, high hydrogen absorption efficiency at low hydrogen concentration, large hydrogen adsorption capacity and high thermal stability, and the hydrogen adsorption capacity at 20°C is about 120ml / g. The amount of refining agent used is 3% of the weight of the magnesium melt.

[0048] 3) The magnesium melt refined in step 2) is heated to 770°C and kept at this temperature for 20 minutes; the resistance furnace is turned off and cooled to 730°C; the magnesium melt is filtered through a porous magnesium oxide ceramic sheet and then cast into a preheated ingot mold to obtain a heat-treatment-free die-cast magnesium alloy; the pore size of the porous magnesium oxide ceramic sheet is 40ppi and the thickness of the ceramic sheet is 30mm.

[0049] The present embodiment is a reproducible heat-treatment-free high-strength and tough die-cast magnesium alloy. The weight percentages of the components are Al: 6.0%, Y: 6.0%, Mn: 1.0%, Zr: 0.5%, Fe: 0.15%, Si≤0.001%, Ni≤0.001%, and the balance is Mg. The die-cast magnesium alloy phases of the present embodiment include a quasi-spherical matrix α-Mg solid solution, a lamellar Al4Y precipitation phase, an Al2Y particle precipitation phase, and a Zr2Fe particle phase. The synergistic effects of solid solution strengthening, fine grain strengthening and dispersion strengthening of high thermal stability precipitation phases brought about by spherical α-Mg solid solution with a size of 2 to 6 μm, lamellar Al4Y precipitation phase with a lamellar spacing of 80 to 100 nm, particle precipitation phase Al2Y with a size of 200 to 500 nm, and Zr2Fe particles with a median particle size of 1 μm make the die-cast magnesium alloy have high strength and toughness comprehensive characteristics. The die-cast tensile strength of the die-cast magnesium alloy in this embodiment is 295 MPa, the yield strength is 188 MPa, and the elongation is 8.5%; the hydrogen content of the die-cast magnesium alloy is 0.2 ml / 100 g Mg, and the inclusion volume fraction is 0.06%. Comparative Example

[0050] The method for preparing the die-cast magnesium alloy of this comparative example comprises the following steps:

[0051] 1) Put the recycled magnesium ingot, aluminum and aluminum-manganese master alloy into a crucible of an argon-protected resistance furnace, heat it to 710°C, add rare earth Ce after the charge is completely melted, and stir evenly for 20 minutes to obtain a magnesium melt;

[0052] 2) The magnesium melt is heated to 740℃ for refining, and the refining agent is evenly sprayed into the magnesium melt with argon gas and maintained for 15 minutes. After the spraying is completed, the slag is removed and the magnesium melt is left to stand for 13 minutes; the spraying speed of the refining agent is 0.8kg / min, and the argon pressure is 0.4MPa; the refining agent is composed of the following components in weight fractions: CaCl2: 34%, BaCl2: 10%, CaF2: 8%, MgCO3: 6%, MgBr2: 12%, and the balance is KCl; the refining agent is prepared by mixing the components according to the corresponding percentages, loading them into a ball mill with a rotation speed of 200r / min, mixing and grinding them into powder, and then passing through a 30-mesh sieve. The amount of the refining agent is 2% of the weight of the magnesium melt.

[0053] 3) The magnesium melt refined in step 2) is heated to 760°C and kept at this temperature for 15 minutes; the resistance furnace is turned off and cooled to 715°C; the magnesium melt is filtered through a porous magnesium oxide ceramic sheet and then cast into a preheated ingot mold to obtain a die-cast magnesium alloy; the pore size of the porous magnesium oxide ceramic sheet is 30ppi and the thickness of the ceramic sheet is 25mm.

[0054] The weight percentage of each component of the die-cast magnesium alloy in this comparative example is Al: 4.0%, Ce: 4.5%, Mn: 0.6%, Zr: 0.3%, Fe≤0.001%, Si≤0.001%, Ni≤0.001%, and the balance is Mg. The phases of the die-cast magnesium alloy in this embodiment include a quasi-spherical matrix α-Mg solid solution, a lamellar Al4Ce precipitation phase, and an Al2Ce particle precipitation phase. The grain size of the quasi-spherical α-Mg solid solution is 2 to 6μm, the interlamellar spacing of the lamellar Al4Ce precipitation phase is 80 to 100nm, and the particle size of the precipitation phase Al2Ce is 200 to 500nm; the die-cast tensile strength of the magnesium alloy in this comparative example is 236MPa, the yield strength is 142MPa, and the elongation is 7.2%. The hydrogen content of the die-cast magnesium alloy is 8.4ml / 100g Mg, and the inclusion volume fraction is 0.25%;

[0055] It can be seen that compared with Example 2, since the Zr2Fe "pump hydrogen" alloy is not added to the comparative refining agent, the diffusion rate of hydrogen in the magnesium liquid is reduced, and even after the refining treatment of the traditional refining agent, efficient dehydrogenation and degassing cannot be achieved, and the high hydrogen content in the magnesium liquid leads to a significant increase in the slag content, resulting in a significant decrease in the toughness of the obtained die-cast magnesium alloy. The hydrogen content and slag content in the magnesium liquid are directly related, and the hydrogen reduction and slag removal measures are mutually integrated and inseparable, as shown in the performance index comparison in Table 1 below.

[0056]

Claims

1. A renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy, characterized in that: The weight percentages of the components in the die-cast magnesium alloy are Al: 3.0-6.0%, RE: 4.0-6.0%, Mn: 0.2-1.0%, Zr: 0.1-0.5%, Fe: 0.03-0.15%, Si≤0.001%, Ni≤0.001%, the balance is Mg, and RE is selected from any one of the rare earths La, Ce and Y; The die-cast magnesium alloy phases include a quasi-spherical matrix α-Mg solid solution, a lamellar Al4RE precipitation phase, an Al2RE particle precipitation phase and a Zr2Fe particle phase; the grain size of the quasi-spherical α-Mg solid solution is 2 to 6 μm, the lamellar spacing of the lamellar Al4RE precipitation phase is 80 to 100 nm, the particle size of the precipitation phase Al2RE is 200 to 500 nm, and the median particle size of the Zr2Fe particles is 1 μm; the die-cast tensile strength of the die-cast magnesium alloy is 268 to 295 MPa, the yield strength is 160 to 188 MPa, and the elongation is 8.5 to 22%; the hydrogen content of the die-cast magnesium alloy is less than 0.5 ml / 100 g Mg, and the inclusion volume fraction is less than 0.1%.

2. A method for preparing a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy as claimed in claim 1, characterized in that: The following steps are involved: 1) Put the recycled magnesium ingot, aluminum and aluminum-manganese master alloy into a crucible of an argon-protected resistance furnace, heat it to 700-730°C, add the rare earth metal element after the charge is completely melted, and stir evenly for 15-30 minutes to obtain a magnesium melt; 2) The magnesium melt is heated to 730-750° C. for refining, and a refining agent is evenly sprayed into the magnesium melt with argon gas and maintained for 10-20 minutes. After the spraying is completed, the slag is removed and the magnesium melt is allowed to stand for 10-15 minutes; the spraying speed of the refining agent is 0.5-1.2 kg / min, and the argon gas pressure is 0.2-0.6 MPa; 3) heating the magnesium melt refined in step 2) to 750-770° C. and keeping the temperature for 10-20 minutes; The resistance furnace is powered off and cooled to 700-730°C; the magnesium melt is filtered through a porous magnesium oxide ceramic sheet and then cast into a preheated ingot mold to obtain a heat-treatment-free die-cast magnesium alloy.

3. The method for preparing a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy according to claim 2, characterized in that: The refining agent is composed of the following components in weight fractions: CaCl2 20~40% BaCl2 6~15% CaF2 5~10% MgCO3 5~7% Bromide 8~15% Zr2Fe alloy 3~6% The balance was KCl.

4. The method for preparing a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy according to claim 2, characterized in that: The amount of the refining agent in step 2) is 1.5-3% of the weight of the magnesium melt.

5. The method for preparing a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy according to claim 2, characterized in that: The pore size of the magnesium oxide porous ceramic sheet in step 3) is 20-40 ppi, and the thickness of the ceramic sheet is 20-30 mm.

6. The method for preparing a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy according to claim 3, characterized in that: The Zr2Fe alloy is a powder particle with a median particle size of 1 μm obtained by repeatedly smelting three times in a magnetic suspension smelting furnace and then ball milling and sieving; the bromide is any one of MgBr2 and CaBr2.

7. The method for preparing a renewable heat-treatment-free high-strength and toughness die-cast magnesium alloy according to claim 3, characterized in that: The refining agent is prepared by mixing the components according to corresponding percentages, loading them into a ball mill with a rotation speed of 100-300 r / min, grinding them into powder, and then passing through a 20-40 mesh sieve.

Citation Information

Patent Citations

  • New process for purifying magnesium alloy

    CN102672148B

  • Method for purifying rare earth magnesium alloy melt

    CN116334432A

  • High-toughness Mg-Al-La-Gd-Zr heat-resistant magnesium alloy and preparation method thereof

    CN117947323A

Cited By

  • Heat-treatment-free high-toughness high-corrosion-resistance magnesium alloy and preparation method thereof

    CN120866703A

  • A heat treatment free high strength and toughness high corrosion resistant magnesium alloy and a preparation method thereof

    CN120866703B